Penyelesaian Sengketa Equity Crowdfunding Syariah Melalui Kelembagaan Alternative Dispute Resolution Terintegrasi - Pratama, Herdifa (Syi`ar Iqtishadi : Journal of Islamic Economics, Finance and Banking, 2024)
The proliferation of Islamic financial institutions and economic activities in Indonesia is an indicator that shows a positive trend of sharia economic development. In fact, these developments began to collaborate with technology to create the innovations in Islamic economic activities. One of them is sharia equity crowdfunding. On the other hand, the rapid development also increases the potential for sharia economic disputes. This is where the active role of dispute resolution institutions is needed. Settlement of these disputes, among others, can be resolved at the Alternative Dispute Resolution Institution. The writing of this article aims to explain the institutions of alternative dispute resolution in Indonesia today through the issuance of POJK No. 61/POJK.07/2020. The main focus of this article is a description of the mechanisms needed in resolving sharia crowdfunding disputes through ADR institutions. This writing ends with an analysis of the advantages and problems contained in the settlement of sharia crowdfunding disputes through ADR institutions.